2018
DOI: 10.1111/jeu.12688
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii, Neospora caninum and Encephalitozoon cuniculi in Animals from Captivity (Zoo and Circus Animals)

Abstract: Problems with parasitic infections are common in zoological gardens and circuses. In some animals it can lead to several disorders such as systemic disease, reproductive disorders (abortions and neonatal mortality), and even to death if severe illness is untreated. Thus, the aim of this study was to evaluate the prevalence of three common parasites in 74 animals from three zoos, and four circuses in Southern Italy. Antibodies to Toxoplasma gondii, Neospora caninum, and Encephalitozoon cuniculi were detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
(34 reference statements)
2
7
0
Order By: Relevance
“…To our knowledge, T. gondii seropositivity in the insectivorous member of the family Hyaenidae, the aardwolf ( Proteles cristatus ) is unknown, but it may be that seropositivity in aardwolves is lower than in carnivorous hyena species. Consistent with the idea of the importance of diet, carnivorous birds have higher T. gondii seropositivity than other bird species (Cabezón et al., 2011), and carnivorous mammals in zoos and circuses in Italy have higher seropositivity than herbivorous mammals (Marková et al., 2018).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…To our knowledge, T. gondii seropositivity in the insectivorous member of the family Hyaenidae, the aardwolf ( Proteles cristatus ) is unknown, but it may be that seropositivity in aardwolves is lower than in carnivorous hyena species. Consistent with the idea of the importance of diet, carnivorous birds have higher T. gondii seropositivity than other bird species (Cabezón et al., 2011), and carnivorous mammals in zoos and circuses in Italy have higher seropositivity than herbivorous mammals (Marková et al., 2018).…”
Section: Discussionsupporting
confidence: 65%
“…(2001)CaptiveChina6/6 (100)MATYang et al. (2017)CaptiveCzech Republic2/2 (100)IFATSedlak and Bártová (2006)CaptiveItaly13/14 (93)IFATMarková et al. (2018)CaptiveMexico7/7 (100)MATAlvarado-Esquivel et al.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding risk factors and conditions that favor infection, the immunocompromised health status of the individual has been described as the main factor favoring infection by this opportunistic agent (Didier 2005 ), but other factors have been reported in animals and humans. For example, in animals, some housing and food conditions have been highlighted: the rearing on household farms, in contrast to commercial farms, due to the less hygienic-sanitary conditions normally found in the first places (Wang et al 2018 ); the use of multi-animal communal cages due to the higher animal density and the consequent contact with urine and feces from other animals (Okewole 2008 ); the fruit-, vegetable-, and grain-based diets due to the potential contamination of these foods (Wang et al 2018 ; Marková et al 2019 ); the outdoor life as stray/feral animals instead of exclusive indoor life like pet animals (Addie et al 2020 ); and keeping animals in stable systems rather than on pasture or in paddocks (Wagnerová et al 2012 ). In humans, other risk factors have been suggested: working with animals and animal products (Halánová et al 2003 ); handling animals and washing their cages due to the potential contact with the urine of infected individuals (Ozkan et al 2011 ; Sak et al 2011b ; Carhan et al 2015 ); living in poor sanitary conditions (Halánová et al 2013 ); and outdoor activities in wildlife habitats, since wild animals are considered reservoirs of this disease (Murphy et al 2007 ; Meredith et al 2015 ).…”
Section: Potential Transmission Routes Environmental Resistance and R...mentioning
confidence: 99%
“…Previous studies have reported the occurrence of coinfection with these agents in domestic mammals such as dogs, 26 wild animals such as rabbits (Oryctolagus cuniculus), 27 as well as wild animals kept in captivity, such as lions (Panthera leo), tigers (Panthera tigris), and reindeer (Rangifer tarandus). 28 A necropsied animal (M1022/18) showed structures similar to protozoan bradyzoites in the histopathological examination of the lung, and the presence of DNA from T. gondii and N. caninum was detected by PCR; thus, the molecular diagnosis was congruent with the positive findings of the immunohistochemistry for T. gondii. The association of these techniques helps in the diagnosis of protozoan etiological agents in primates.…”
Section: Discussionmentioning
confidence: 81%
“…caninum , demonstrating coinfection in both free‐living (one Mico melanurus and one Aotus azarae ) and captive (one Sapajus apella ) animals. Previous studies have reported the occurrence of coinfection with these agents in domestic mammals such as dogs, 26 wild animals such as rabbits ( Oryctolagus cuniculus ), 27 as well as wild animals kept in captivity, such as lions ( Panthera leo ), tigers ( Panthera tigris ), and reindeer ( Rangifer tarandus ) 28 …”
Section: Discussionmentioning
confidence: 99%